Diagnósticos de Enfermagem em pacientes oncológicos com feridas - Queiroz , Patrícia Lima (2016)
Cancer is a genetic disease whose initiation and progression involves a series of lesions in the DNA or aberrant expression of normal genes and has become relevant as a public health problem in Brazil,due to the high and increasing incidence of mortality. Studies show that 5% to 10% of patients with metastatic cancer in the last six months of life develop wounds. The wounds in cancer patients, reflected in psychosocial, biological and spiritual implications. The systematization of nursing care through the nursing process makes nurses use clinical reasoning and critical judgment for identification and inventory of problems. The nursing diagnosis is the second stage of this process, and is focused on individual responses to the disease, health processes and/or factors affecting the maintenance of the individual balance. This research aimed to develop nursing diagnosis for the International Classification for Nursing Practice(ICNP®)in cancer patients with wounds.It was developed a descriptive, cross-sectional, exploratory research methodology and a quantitative approach, conducted from August to October 2015,in an oncology reference hospital,with the participation of 30 hospitalized patients,using the theoretical framework of the Basic Human Needs Theory from Wanda Horta and following the guidelines for the preparation of Nursing Diagnoses,proposed by ISO18104:2014 and the terms contained in the axles focus and judgment of ICNP® version 2015.The implementation of the research was divided into five phases: 1) survey of cancer patients with and without wounds; 2) application of nursing history and physical examination; 3) identification and evaluation of wounds; 4)identification of nursing phenomena; and 5)the preparation of statements of nursing diagnoses.The research was discussed and approved by the Ethics Committee of the Federal University of Maranhão,according to resolution no. 466/2012 of the National Health Council, under opinion Nº.1.161.269 and Nº.CAEE 44080115.3.0000.5087. After tab in Microsoft Excel ®2007 program, the data allowed representation in proportion and frequency distribution and the development of nursing diagnoses,according to the combination of terms of axles Focus and Judgment contained in ICNP®. We obtained the following results: the prevalence of wounds in male patients,aged 49-59 years old, brownskinned color, from the interior of the state, married, incomplete primary education, income up to 2 minimum wages, farmers, evangelical and on admission to hospital for pain, through the hospital emergency department; identification of 50 wounds being prevalent neoplastic, surgical and pressure ulcers; prevalence of breast and and penis cancer diagnoses and the preparation of 242 nursing diagnoses,188 belonging to the category of physiological needs, 49 of Psychosocial and 5 psychospiritual. It is considered that this study may contribute to the practice of oncology nursing, in order to sustain the scientific knowledge and the development of nursing care abilities to this clientele and to direct the nursing staff for a development of an individualized,systematic, comprehensive care and of universal language.